A supported catalyst for growing array-type carbon nanotubes and a preparation method thereof
By adding cationic surfactants and water vapor treatment during the catalyst preparation process, the problem of low -growth rates caused by catalysts in the existing technologies without direct impregnation, and achieve efficient growth and excellent performance of array -type carbon nanotubes.
Patent Information
- Application Number
- CN202410829924.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-06-25
AI Technical Summary
Prior Art When preparing array carbon nanotubes by chemical vapor deposition method, direct impregnation of the catalyst without treatment leads to a lower growth rate.
The preparation method of the load catalyst is used to mix the carrier front drive body with the cationic surfactant to perform water vapor treatment and rotation and evaporation reactions, adjust the pH value and temperature, and prepare catalysts with excellent catalytic performance.
It significantly improves the growth rate of array -type carbon nanotubes, the uniformity of diameter and high conductivity, and the particle size and interface performance of the catalyst have also been optimized.
Smart Images

Figure CN118807770B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon nanotubes and catalysts thereof, and in particular relates to a supported catalyst for growing array-type carbon nanotubes and a preparation method thereof. Background Art
[0002] Carbon nanotubes, also known as buckytubes, are a tubular structure in which the basic unit of graphene is a regular hexagon. The length is between a few microns and tens of microns, but the radial size is nanometers. It is a one-dimensional quantum material with unique physical structure and chemical properties. The remarkable high mechanical strength, thermal conductivity and electrical conductivity of carbon nanotubes make ultra-fine carbon nanotubes have great application value in composite materials, biomaterials and electronic components.
[0003] Array-type carbon nanotubes have a relatively uniform aspect ratio, excellent orientation and purity, which are conducive to better performance of carbon nanotubes. Studies have shown that after array-type carbon nanotubes are destroyed and used in the fields of electrical conductivity, thermal conductivity and composite materials, their performance is still better than that of general carbon nanotubes.
[0004] The preparation of array-type carbon nanotubes by chemical vapor deposition has high requirements for catalysts. Natural minerals with layered structures can be used as carriers for growing array-type carbon nanotube catalysts. However, the growth rate of carbon nanotubes prepared by directly impregnating and loading the catalysts without treatment is generally low.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide a supported catalyst for growing array-type carbon nanotubes and a preparation method thereof, so as to solve the above-mentioned problems.
[0007] In order to achieve the above objectives, the present invention particularly adopts the following technical solutions:
[0008] The present invention provides a method for preparing a supported catalyst for growing array-type carbon nanotubes, the preparation method comprising the following steps:
[0009] S1: dispersing a carrier precursor into an aqueous solution of a cationic surfactant to obtain a solution A; the carrier precursor includes any one of calcium-based montmorillonite, sodium-based montmorillonite, sodium-calcium-based montmorillonite, and magnesium-based montmorillonite;
[0010] The cationic surfactant includes one or more of amine salt type, quaternary ammonium salt type, heterocyclic type and pyrochlore salt type;
[0011] S2: dissolving active component raw materials in water to obtain solution B; the active component raw materials include one or more of cobalt nitrate, copper nitrate, chromium nitrate, manganese nitrate, nickel nitrate, and iron nitrate;
[0012] Preferably, the solute of the solution B includes a plurality of the active component raw materials; further preferably, the solute of the solution B is a mixture of iron nitrate, nickel nitrate and manganese nitrate in a mass ratio of 2-5:0.1-2:0.2-3;
[0013] S3: adding solution B obtained in S2 to solution A obtained in S1 and mixing evenly, adjusting the pH value to 7-11 and reacting at a temperature of 40-95° C. for 1-10 h; preferably, the pH value is 8-10, the temperature is controlled at 70-90° C., and the aging time is 2-5 h;
[0014] The mixing is carried out in a rotary evaporation reactor, and the rotation speed of the rotary evaporation reactor is 10 to 200 rpm / min;
[0015] The mixing temperature is 40 to 95° C.
[0016] S4: Heat the reaction product of S3 to 200-300°C and maintain for 2-3 hours to obtain.
[0017] Preferably, the step S4 further comprises grinding the obtained catalyst to 30-150 meshes to obtain catalyst fine powder.
[0018] Preferably, the preparation method further comprises: pretreating the carrier precursor;
[0019] The pretreatment includes a first pretreatment, which includes: crushing the carrier precursor to 100 mesh or above, dissolving it in water and stirring it for 2 to 3 hours, standing it for 0.5 to 1 hour to obtain a slurry, washing it for 3 to 6 times, filtering it, and drying it naturally;
[0020] The mass concentration of the slurry 1 is 8-20%.
[0021] Further preferably, the pretreatment further comprises a second pretreatment, wherein the second pretreatment comprises: dissolving the first pretreatment product in water again to prepare a second slurry, then adding a sodiumizing agent to the second slurry, ultrasonically treating at 60 to 95° C. for 1 to 2 hours, and then filtering, drying, and grinding;
[0022] The mass of the sodiumizing agent is 1 to 9% of the mass of the first pretreated product;
[0023] The mass concentration of the second slurry is 8-20%.
[0024] More preferably, the pretreatment further includes a third pretreatment, and the third pretreatment includes: placing the second pretreatment product in a high-pressure reactor and introducing 0.3-1.2 MPa steam from bottom to top to steam it for 1-6 hours.
[0025] The present invention also provides a process for producing array-type carbon nanotubes using a supported catalyst prepared by the preparation method, wherein the composition of the catalyst, in terms of mass percentage, comprises: 1 to 50% active component and 10 to 80% carrier;
[0026] The ratio of array-type carbon nanotubes prepared by chemical vapor deposition using the catalyst is 20 to 50 times.
[0027] The chemical vapor deposition method comprises: heating a fluidized bed reactor to 600-800° C., adding the catalyst, uniformly adding a raw gas and a carrier gas, reacting for a period of time, adding a reducing gas, and obtaining a black fluffy solid after the reaction is completed, and then sequentially purifying, acid washing, and water washing to obtain an array-type carbon nanotube;
[0028] The raw gas includes one or more of methane, ethane, propane, butane, acetone, methanol, ethanol, and propylene;
[0029] The carrier gas includes any one of nitrogen, helium and argon.
[0030] Different from the preparation method of conventional catalysts, the present invention uses montmorillonite as a carrier precursor to prepare a supported catalyst, and in the process of carrier preparation, a cationic surfactant is added to treat the catalyst carrier by utilizing its anti-aggregation and anti-coagulation capabilities, thereby controlling the particle size and interface properties of the final catalyst. The ionic surfactant can effectively reduce the surface tension of the system, and in the rotary evaporation reaction, can reduce the liquid film thickness to a greater extent, thereby increasing the interface evaporation rate and reducing the control temperature, thereby achieving the purpose of energy saving and efficiency improvement.
[0031] The cationic surfactant used in the present invention can be a small molecule ionic surfactant, or a polymer and natural macromolecular cationic surfactant. Among them, the polymer cationic surfactant has a stronger electrostatic interaction relationship, better anti-aggregation and coagulation ability, and the prepared catalyst performance is the most ideal.
[0032] In addition, the addition of ionic surfactants can reduce the surface tension of the system. In the subsequent rotary evaporation reactor, the liquid film thickness can be reduced to a greater extent, the interfacial evaporation rate can be increased, and the control temperature can be reduced, thereby achieving the purpose of energy saving and efficiency improvement.
[0033] Beneficial effects of the present invention:
[0034] The preparation method of the catalyst provided by the present invention is different from the conventional direct impregnation loading. The present invention effectively improves the pore structure of the carrier precursor through pretreatment methods such as water vapor treatment and cationic surfactant treatment, and combines rotary evaporation coating to improve the dispersion of active components, thereby effectively improving the structure and catalytic performance of the catalyst. The prepared catalyst is used for the growth of array-type carbon nanotubes, which can significantly increase the growth rate of carbon nanotubes.
[0035] The core metal and carrier structure of the catalyst provided by the present invention can be precisely controlled, so that the diameter of the array-type carbon nanotubes deposited and grown on the catalyst prepared by the present invention is 4 to 10 nm, the tube length is 10 to 40 μm, the powder conductivity is as high as 18000 S / m or more, and the growth rate is 20 to 50 times. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 This is an appearance morphology diagram of the catalyst provided in Example 1;
[0038] Figure 2 This is a morphological diagram of the carbon nanotubes grown using the catalyst provided in Example 1;
[0039] Figure 3 This is an appearance morphology diagram of the catalyst provided in Example 2;
[0040] Figure 4 This is a morphological diagram of the carbon nanotubes grown using the catalyst provided in Example 2;
[0041] Figure 5 This is an appearance morphology diagram of the catalyst provided in Example 3;
[0042] Figure 6 This is a morphological diagram of the carbon nanotubes grown using the catalyst provided in Example 3;
[0043] Figure 7 This is an appearance morphology diagram of the catalyst provided in Example 4;
[0044] Figure 8 This is a morphological diagram of the carbon nanotubes grown using the catalyst provided in Example 4. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0046] Example 1
[0047] This embodiment provides a method for preparing a supported catalyst for growing array-type carbon nanotubes, and the specific steps are as follows:
[0048] S1: Take 500g of calcium-based montmorillonite and crush it to more than 100 mesh, disperse it in deionized water, prepare a slurry with a mass concentration of 14%, stir it for 2h, let it stand for 0.5h, remove larger particles, wash it 3 times, filter it and dry it naturally;
[0049] S2: The dried product obtained in S1 was prepared into a slurry 2 with a concentration of 14% using deionized water, and then sodium carbonate was added to the slurry 2, and the mass of the sodium carbonate was controlled to be 2% of the mass of the dried product of S1, and the slurry 2 was ultrasonically treated at 80°C for 1h, filtered, dried at 80°C, and ground;
[0050] S3: The ground product obtained in S2 is placed in a high-pressure reactor, and 0.3 MPa steam is introduced from bottom to top to treat it for 2 hours. After the treatment, the obtained product is dispersed in deionized water added with an amine salt type cationic surfactant, and prepared into solution A by ultrasonication;
[0051] S4: Active components of ferric nitrate, nickel nitrate and manganese nitrate were mixed in a mass ratio of 2:0.1:3, and then 150 g of the active component mixture was dissolved in deionized water to prepare solution B;
[0052] S5: Add solution A to the rotary evaporation reactor, and drop solution B into the reactor at a rotation speed of 100 rpm / min, control the temperature at 80°C, adjust the pH value to 8 after the dropwise addition, and keep the temperature for aging reaction for 3 hours;
[0053] S6: The rotary evaporation reactor is heated to 260° C. and maintained at this temperature for 2 hours, and the solid product is ground into a fine powder of 30 to 150 meshes to obtain the catalyst.
[0054] The method of preparing carbon nanotubes using the obtained catalyst comprises the following steps:
[0055] The fluidized bed reactor was heated to 800°C, the catalyst obtained from S6 was added, and then methane gas was evenly added with nitrogen as the carrier gas. After a period of reaction, hydrogen was added as the reducing gas. After the reaction was completed, a black fluffy solid was obtained, which was then purified, acid-washed, and water-washed in sequence to obtain array-type carbon nanotubes.
[0056] The appearance morphology of the catalyst obtained in this example is shown in Figure 1 As shown by Figure 1 It can be seen that the catalyst prepared in this example has uniform particle size and a dense appearance. The appearance morphology of the carbon nanotubes produced using the obtained catalyst is shown in FIG. Figure 2 As shown by Figure 2 It can be seen that the produced carbon nanotube array is neat, the tube diameter is uniform, and the aspect ratio is relatively large.
[0057] Example 2
[0058] The difference from Example 1 is that step S3 of this embodiment does not include steam treatment, that is, step S3 of this embodiment is:
[0059] The ground product obtained in S2 is dispersed in deionized water to which an amine salt type cationic surfactant is added, and is prepared into solution A by ultrasonication;
[0060] The remaining steps are the same as those in Example 1.
[0061] The appearance morphology of the catalyst obtained in this example is shown in Figure 3 As shown by Figure 3 It can be seen that the surface uniformity of the prepared catalyst is poor and there is a breakage phenomenon; the appearance morphology of the carbon nanotubes prepared using the obtained catalyst is shown in Figure 4 As shown by Figure 4 It can be seen that the produced carbon nanotube array is slightly inferior, and the proportion of wound tubes is relatively large.
[0062] Example 3
[0063] The difference from Example 1 is that, in step S3 of this embodiment, no cationic surfactant is added when preparing solution A, that is, S3 of this embodiment is:
[0064] The ground product obtained in S2 was placed in a high-pressure reactor, and 0.3 MPa steam was introduced from bottom to top for 2 hours. After the treatment, the obtained product was dispersed in deionized water and prepared into solution A by ultrasonication;
[0065] The remaining steps are the same as those in Example 1.
[0066] The appearance morphology of the catalyst obtained in this example is shown in Figure 5 As shown by Figure 5It can be seen that the surface uniformity of the prepared catalyst is poor; the appearance morphology of the carbon nanotubes prepared using the obtained catalyst is shown in Figure 6 As shown by Figure 6 It can be seen that the carbon nanotube array produced is acceptable, and a small amount of entangled tubes are still generated.
[0067] Example 4
[0068] The difference from Example 1 is that the order of pretreatment in preparing solution A in step S3 of this embodiment is different, specifically:
[0069] S3: The ground product obtained in S2 is dispersed in deionized water to which an amine salt type cationic surfactant is added, and after sufficient stirring, it is filtered, dried, and ground. The ground product is then placed in a high-pressure reactor and treated with 0.3 MPa steam from bottom to top for 4 hours. After the treatment, the obtained product is dispersed in deionized water and prepared into solution A using ultrasound;
[0070] The remaining steps are the same as those in Example 1.
[0071] The appearance morphology of the catalyst obtained in this example is shown in Figure 7 As shown by Figure 7 It can be seen that the surface uniformity of the prepared catalyst is poor; the appearance morphology of the carbon nanotubes prepared using the obtained catalyst is shown in Figure 8 As shown by Figure 8 It can be seen that the produced carbon nanotube array is poor and the proportion of wound tubes is too large.
[0072] The carbon nanotubes prepared in the above examples 1-4 were subjected to performance tests, and the standards implemented in the tests were: GB / T26826-2011-Method for measuring the diameter of carbon nanotubes; GB / T 33243-2016-Nanotechnology-Characterization of multi-walled carbon nanotubes; GB / T 32871-2016-Raman spectroscopy for characterization of single-walled carbon nanotubes; GB / T 37152-2018-Nanotechnology-Carbon nanotube materials-Sheet resistance. The performance test results of the carbon nanotubes prepared in examples 1-4 are shown in Table 1 below:
[0073] Table 1 Performance test results of carbon nanotubes prepared in Examples 1-4
[0074] project Pipe diameter nm Tube length μm Conductivity S / m <![CDATA[Specific surface area m 2 / g]]> magnification Example 1 4~10 10~40 >18000 >400 20~50 Example 2 10~30 5~30 >8000 >300 10~30 Example 3 10~20 5~30 >10000 >300 20~40 Example 4 15~30 5~25 >6000 >200 10~20
[0075] As can be seen from Table 1, the carbon nanotubes prepared by the method provided in Example 1 have a smaller diameter, higher conductivity, and a larger rate, showing better comprehensive performance. Since the catalyst provided in Example 1 first shows better appearance performance, and then shows better catalytic performance when used in the fluidized bed synthesis of carbon nanotubes, under the condition that other conditions are basically the same, the catalyst prepared in Example 1 of the present application has uniform appearance, and in the production process of carbon nanotubes, the performance is more outstanding, and the performance of the prepared carbon nanotubes is more superior.
[0076] By comparing Example 1 and Example 2, it can be seen that the volume of the carrier montmorillonite can expand several times after adding water and become a paste, and the volume shrinks after being heated and dehydrated. According to this property of montmorillonite, steam is used to treat it, so that the montmorillonite repeats between volume expansion due to water absorption and shrinkage due to thermal dehydration, and by controlling process conditions such as steam pressure, flow rate, and stripping time, the state of montmorillonite is further refined and controlled to achieve the properties required by the present invention; the steam pressure selected by the present invention is conventional saturated steam, which is simple and easy to obtain. A high steam pressure increases the cost, and a low steam pressure results in unsatisfactory carrier treatment, which increases the amount of paste.
[0077] By comparing Example 1 and Example 3, it can be seen that since montmorillonite itself is insoluble in water, in order to improve its dispersibility as a carrier in the aqueous phase, to prevent and avoid the aggregation and agglomeration of the carrier, thereby affecting the particle size and interfacial properties of the final catalyst. By using the electrostatic repulsion generated by the zeta potential of the cationic surfactant and the carrier in the aqueous phase, the dispersion effect of the carrier dispersion is strengthened, its agglomeration tendency is weakened, the particle size of its hydrated particles is minimized as much as possible, and it is also beneficial to avoid the coagulation of the carrier in the aqueous phase, thereby ensuring that the prepared catalyst has a smaller particle size and a more monodispersed particle size distribution, thereby significantly improving the comprehensive performance of the catalyst.
[0078] By comparing Example 1 and Example 4, it can be seen that the same pretreatment method, but different pre-treatment sequences, has an obvious impact on the results, because the active components are dispersed in the montmorillonite carrier that has not been steam-treated with the help of the added cationic surfactant, and after the corresponding treatment steps, the obtained catalyst is treated with steam. Also, since the volume of montmorillonite can expand several times after adding water and become a paste, and its volume shrinks after being heated and dehydrated, the active components of the catalyst finally obtained are unevenly dispersed, resulting in performance deviations of carbon nanotubes produced using the catalyst.
[0079] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.
Claims
1. A method for preparing a supported catalyst for growing array-type carbon nanotubes, characterized in that: The preparation method comprises the following steps: S1: dispersing the pretreated support precursor into an aqueous solution of a cationic surfactant to prepare a solution A; S2: dissolving the active ingredient raw material in water to prepare solution B; S3: adding the solution B obtained in S2 to the solution A obtained in S1, mixing evenly, adjusting the pH value and reacting; S4: Heat the reaction product of S3 to 200-300°C and maintain for 2-3 hours to obtain; The preprocessing includes a first preprocessing, a second preprocessing and a third preprocessing: The first pretreatment comprises: crushing the carrier precursor to 100 mesh or above, dissolving it in water and stirring it for 2-3 hours, standing it for 0.5-1 hour to obtain a slurry with a mass concentration of 8-20%, washing it 3-6 times, filtering it, and drying it naturally; The second pretreatment comprises: dissolving the first pretreatment product in water again to prepare a slurry 2 with a mass concentration of 8-20%, then adding a sodium agent to the slurry 2, ultrasonically treating at 60-95° C. for 1-2 hours, and then filtering, drying, and grinding; wherein the mass of the sodium agent is 1-9% of the mass of the first pretreatment product; The third pretreatment comprises: placing the second pretreatment product in a high pressure reactor and introducing 0.3-1.2 MPa steam from bottom to top to perform steam treatment for 1-6 hours; The carrier precursor includes any one of calcium-based montmorillonite, sodium-based montmorillonite, sodium-calcium-based montmorillonite, and magnesium-based montmorillonite; The cationic surfactant includes one or more of amine salt type and quaternary ammonium salt type; The active component raw materials include one or more of cobalt nitrate, copper nitrate, chromium nitrate, manganese nitrate, nickel nitrate and iron nitrate.
2. The preparation method according to claim 1, characterized in that: In S3, the mixing is performed in a rotary evaporation reactor, and the rotation speed of the rotary evaporation reactor is 10-200 rpm / min; The mixing temperature is 40-95°C.
3. The preparation method according to claim 1, characterized in that: In said S3, the pH value shown is 7 to 11; The reaction is an aging reaction, the temperature of the aging reaction is 40-95° C., and the time is 1-10 hours.
4. A supported catalyst for growing array-type carbon nanotubes prepared by the preparation method according to any one of claims 1 to 3, characterized in that: The composition of the catalyst, in terms of mass percentage, includes: 1-50% active component and 10-80% carrier; The growth rate of array-type carbon nanotubes prepared by chemical vapor deposition using the catalyst is 20 to 50 times.
5. The catalyst according to claim 4, characterized in that The chemical vapor deposition method comprises: heating a fluidized bed reactor to 600-800° C., adding the catalyst, uniformly adding a raw gas and a carrier gas, reacting for a period of time, adding a reducing gas, and obtaining a black fluffy solid after the reaction is completed, and then sequentially purifying, acid washing, and water washing to obtain an array-type carbon nanotube; The raw gas includes one or more of methane, ethane, propane, butane, acetone, methanol, ethanol, and propylene; The carrier gas includes any one of nitrogen, helium and argon.
Citation Information
Patent Citations
Preparation method for nickel cobalt / montmorillonite catalyst
CN104148077A
Preparation method of carbon nanotube array materials
CN106927449A